1979
DOI: 10.1002/mrc.1270121006
|View full text |Cite
|
Sign up to set email alerts
|

Tritium nuclear magnetic resonance spectroscopy. Part 11. Further consideration of referencing, isotope effects and coupling constants: Preparation of [3H]tetramethylsilane

Abstract: Small discrepancies between 3H and 1H chemical shifts in organic compounds led to the finding that the ratio of Larmor frequencies ωT/ωH depends on the carbon‐hydrogen bond hybridisation. The ‘best’ ratio for ghost referencing of 3H NMR spectra was then determined from measurements on purified partially tritiated TMS as 1.066639738±2 × 10−9. Some 3H isotope effects on chemical shifts are listed and the 3H isotope effect on the methylene geminal coupling constant in benzyl methyl sulphoxide is measured. Use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…It may be noted that the respective ZJH,H values in the sidechain (Table 1) are apparently equal to those in toluene (18) and in methyl bromide (19). A similar comparison holds for phenylethane (20), toluene, and methane. Because the conformational averages of the H-H vector in the alpha methylene group with respect to the benzene n system must be quite different in the three phenyl compounds, doubt arises about the use of ZJH,H in conformational deductions for benzyl derivatives.…”
Section: I-bromo-(35-dibromophenyl) Ethanementioning
confidence: 51%
“…It may be noted that the respective ZJH,H values in the sidechain (Table 1) are apparently equal to those in toluene (18) and in methyl bromide (19). A similar comparison holds for phenylethane (20), toluene, and methane. Because the conformational averages of the H-H vector in the alpha methylene group with respect to the benzene n system must be quite different in the three phenyl compounds, doubt arises about the use of ZJH,H in conformational deductions for benzyl derivatives.…”
Section: I-bromo-(35-dibromophenyl) Ethanementioning
confidence: 51%
“…These relate to notational matters and are particularly directed at publications in chemical journals. In several places, we use different wording from the original reports and in some cases extended meanings: The nucleus giving rise to the spectrum concerned should always be explicitly stated in full or in abbreviation (e.g., 10 B NMR or boron-10 NMR). The isotopic mass number should be given except in cases without ambiguity.…”
Section: Recommendations Endorsedmentioning
confidence: 99%
“…δ X / ppm = 10 6 (Ξ X,sample -Ξ X,reference ) / Ξ X,reference (10) The widespread use of a 2 H lock for NMR measurements on isotropic samples suggests a modification of the substitution approach, since the relevant reference frequency should not vary with time. Thus, the chemical shifts of the X nuclei can, in principle, be determined on the unified (TMS-based) scale merely by measuring the resonance frequency of the sample and using a predetermined reference frequency for the nuclide in question.…”
Section: Practical Application Of the Unified Scalementioning
confidence: 99%
“…Based on somewhat complex referencing procedures (3,26), it was concluded that aromatic tritons resonate downfield from aromatic protons. The A values in Table 2 appear to confirm this conclusion because the 'H nmr shift of benzene in the appropriate solvent is used to calculate the A values (the shift of in [,HI-benzene relative to the shift of 'H in benzene is apparently unavailable).…”
Section: The Chemical Shifismentioning
confidence: 99%